2010
DOI: 10.2337/db10-0522
|View full text |Cite|
|
Sign up to set email alerts
|

β-Cell Dysfunctional ERAD/Ubiquitin/Proteasome System in Type 2 Diabetes Mediated by Islet Amyloid Polypeptide–Induced UCH-L1 Deficiency

Abstract: OBJECTIVEThe islet in type 2 diabetes is characterized by β-cell apoptosis, β-cell endoplasmic reticulum stress, and islet amyloid deposits derived from islet amyloid polypeptide (IAPP). Toxic oligomers of IAPP form intracellularly in β-cells in humans with type 2 diabetes, suggesting impaired clearance of misfolded proteins. In this study, we investigated whether human-IAPP (h-IAPP) disrupts the endoplasmic reticulum–associated degradation/ubiquitin/proteasome system.RESEARCH DESIGN AND METHODSWe used pancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
97
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 53 publications
10
97
0
Order By: Relevance
“…Inhibition of the UPS system has been reported not only for α-syn oligomers [42,43], but also with toxic assemblies of other amyloidogenic proteins, including Aβ [44] and islet amyloid polypeptide [45,46]. A recent report demonstrated that overexpression of polyglutamine results in transient UPS inhibition in mice, but the activity returned when large inclusions formed [47].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the UPS system has been reported not only for α-syn oligomers [42,43], but also with toxic assemblies of other amyloidogenic proteins, including Aβ [44] and islet amyloid polypeptide [45,46]. A recent report demonstrated that overexpression of polyglutamine results in transient UPS inhibition in mice, but the activity returned when large inclusions formed [47].…”
Section: Discussionmentioning
confidence: 99%
“…heparan sulphate proteoglycans) [24]; inducing endoplasmic reticulum stress [25] and oxidative stress [26]; and disruption of the endoplasmic reticulum-associated degradation (ERAD)/ubiquitin/proteasome system [27] and autophagy/ lysosomal pathway [28]. Although several mechanisms, at least in vitro, are involved in hIAPP-induced beta cell apoptosis, some of these may share the same apoptotic signalling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms have been shown to mediate amyloid-induced beta cell death, including membrane disruption by hIAPP aggregates [15,16], activation of the Fasmediated apoptosis and caspase pathways [7,8,17], interaction of hIAPP aggregates with components of beta cell membranes (such as heparan sulphate proteoglycans [18] or touch receptors [19]), endoplasmic reticulum stress [20,21], oxidative stress [22], activation of the cJUN N-terminal kinase (JNK) pathway [23] and disruption of the autophagy/lysosomal pathway [24]. Growing evidence suggests that small hIAPP aggregates (e.g.…”
Section: Introductionmentioning
confidence: 99%